Agricultural Sustainability: Microbial Biofertilizers in Rhizosphere Management - Fasusi, Oluwaseun Adeyinka; Cruz, Cristina; Babalola, Olubukola Oluranti (Agriculture (Basel), 2021)
The world’s human population continues to increase, posing a significant challenge in ensuring food security, as soil nutrients and fertility are limited and decreasing with time. Thus, there is a need to increase agricultural productivity to meet the food demands of the growing population. A high level of dependence on chemical fertilizers as a means of increasing food production has damaged the ecological balance and human health and is becoming too expensive for many farmers to afford. The exploitation of beneficial soil microorganisms as a substitute for chemical fertilizers in the production of food is one potential solution to this conundrum. Microorganisms, such as plant growth-promoting rhizobacteria and mycorrhizal fungi, have demonstrated their ability in the formulation of biofertilizers in the agricultural sector, providing plants with nutrients required to enhance their growth, increase yield, manage abiotic and biotic stress, and prevent phytopathogens attack. Recently, beneficial soil microbes have been reported to produce some volatile organic compounds, which are beneficial to plants, and the amendment of these microbes with locally available organic materials and nanoparticles is currently used to formulate biofertilizers to increase plant productivity. This review focuses on the important role performed by beneficial soil microorganisms as a cost-effective, nontoxic, and eco-friendly approach in the management of the rhizosphere to promote plant growth and yield.